2018
DOI: 10.1111/bjh.15282
|View full text |Cite
|
Sign up to set email alerts
|

MEK1/2 inhibition by binimetinib is effective as a single agent and potentiates the actions of Venetoclax and ABT‐737 under conditions that mimic the chronic lymphocytic leukaemia (CLL) tumour microenvironment

Abstract: The survival and proliferation of chronic lymphocytic leukaemia (CLL) cells is driven by multiple signalling pathways, including those mediated by the B cell, Toll-like and chemokine receptors. Many of these pathways converge on the same signalling molecules, including those involved in the Raf-1/MEK/Erk1/2-MAPK pathway. We investigated the effects of the MEK1/2 (also termed MAP2K1/2) inhibitor, binimetinib, against CLL cells cultured under conditions that mimic aspects of the tumour microenvironment. Binimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…If the MEKi can be administered as part of a combination regimen, synergy between the agents could justify a reduced drug dose, which may also lower toxicities. Preclinical studies have indicated synergy between MEKi and fludarabine, PI3K inhibitors, and B‐cell lymphoma 2 (Bcl‐2) antagonists in CLL [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…If the MEKi can be administered as part of a combination regimen, synergy between the agents could justify a reduced drug dose, which may also lower toxicities. Preclinical studies have indicated synergy between MEKi and fludarabine, PI3K inhibitors, and B‐cell lymphoma 2 (Bcl‐2) antagonists in CLL [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a strategy to suppress MCL-1 expression by targeting MAPK should sensitize malignant cells to BH3 mimetics, including venetoclax. The MEK1/2 inhibitor binimetinib potentiated the activity of venetoclax and ABT-737 under conditions that mimic the CLL tumor microenvironment via downregulation of MCL-1 activity, BIM and BCL-xL expression 109 .…”
Section: Targeting Mcl-1mentioning
confidence: 99%
“…Stroma-mediated elevations in MCL-1 were associated with increased AKT and MAPK/ERK signaling, which may reduce MCL-1 proteolysis, as well as increased phosphorylation of serine 5 of the RNA polymerase-II C-terminal domain, which is mediated by CDK9 and known to support the elongation of MCL1 transcripts. Other studies support the idea that combinations with MEK ( 35 ) or CDK9 ( 36 38 ) inhibitors could enhance venetoclax activity and circumvent resistance, and ongoing clinical studies in acute myeloid leukemia (AML) may soon provide clinical data (see below).…”
Section: Venetoclax Resistance In Chronic Lymphocytic Leukemiamentioning
confidence: 99%